HIJAB DAN JILBAB DALAM PERSPEKTIF SEJARAH - Rosdiana A Bakar (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Hijab and jilbab the self-esteem of a woman's Women. Hijab previouslydefined a woman's Women should stay at home where their human rights areguaranteed and also show social prestige. In modern times the hijab can beinterpreted with a car that can protect women from the sight and impaired menwho intend evil. This is also the prestige of his time. The hijab is morefundamentally, that distinguishes a respectable woman and not dear or cheap. Inother words the veil to distinguish between women who are obedient to religiousteachings and apostate religious teachings. Similarly, what happened in history.Keywords: Hijab dan Jilbab.